Regulation of paracellular transport in the distal nephron - Hou, Jianghui (2012)
PURPOSE OF REVIEW: Claudins play a major role in the regulation of paracellular electrolyte reabsorption in the kidney. This review describes recent findings of the physiological function of claudins underlying paracellular transport mechanisms for Cl(−) reabsorption in the collecting duct. RECENT FINDINGS: There are two parallel mechanisms for transepithelial Cl(−) reabsorption in the collecting duct that utilize the Na-driven Cl-bicarbonate exchanger (NDCBE) and the claudin-based paracellular channel. Histological studies have demonstrated the renal localization of claudin-3, -4, -7 and -8 in the collecting duct. Molecular analyses using several collecting duct cell models have come to the conclusion that claudin-4 functions as a paracellular Cl(−) channel. The channel function of claudin-4 is conferred by a charged lysine residue (K65) in its extracellular loop. Claudin-8 is required for paracellular Cl(−) permeation through its interaction with and recruitment of claudin-4 during tight junction assembly. Claudin-7 provides the basic barrier function to the collecting duct. Genetic ablation of claudin-7 in animals results in systemic dehydration owing to the loss of extracellular ions and fluid in the kidney. SUMMARY: The paracellular pathway in the collecting duct is an important route for transepithelial Cl(−) reabsorption that determines the extracellular NaCl content and the blood pressure. In the collecting duct cells, claudin-4 and -8 interact to form a paracellular Cl(−) channel while claudin-7 maintains the transepithelial resistance. Different subsets of the claudin family proteins fulfill diverse aspects of the tight junction function that will be fundamental to understanding the physiology of the paracellular pathway.